From the Forgotten Russian Avant-Garde: An Unknown Acrostic by I.A.Aksenov Dedicated to K.A.Bol’shakov. (On IWL RAS Archival Materials) - Alessandro Farsetti (Studia Litterarum)
This is the first publication of a hitherto unknown acrostic by an avant-garde poet, I. A. Aksenov. The poem was found in the archive of the Russian Union of Soviet Writers (VSSP) in the Manuscript Section of the Institute of World Literature (IWL). This poem dated 1918 is a complex example of Russian avant-garde poetry demonstrating subtle mechanisms of meaning-making. The essay places the poem within the context of Aksenov’s work and relates it to his biography (cf. his friendship with a poet, K.A. Bol’shakov, to whom the poem was dedicated and the participation of both in S.G.Kara-Murza’s literary circle “Tuesdays”). It outlines the basic structure of the acrostic, reveals its main linguistic devices and intertextual connections. The analysis shows that the acrostic was thematically connected with two poems Aksenov and Bol’shakov wrote later the same day at Kara-Murza’s house. All the three texts capture the incubus of the Civil war (more precisely, the so called «Red terror» in the Fall of 1918) but also express hope for the return of the normal life, relying on friendship of like-minded people. In addition to this, the essay reveals possible interrelation between poetic techniques of Bol’shakov and Aksenov; this will enable us to better understand the specificity of these two understudied representatives of Russian avant-garde.